Dermatologic Emergencies CME Part II: Infections and infection-related complications - Mohammed Shanshal (Our Dermatology Online, 2022)
This section covers the strategies for managing the dermatologic infectious diseases and how they present in emergency and acute settings. In order to keep the staff and patients safe, emergency physicians should be able to limit the nosocomial infection spread.